Ontological status gnome in the theological opus of saint Maximus the Confessor - Stevanović, Nebojša (Sabornost, 2022)
The question of the gnome in the theological opus of saint Maximus the Confessor represents a hermeneutic code for a proper understanding of diothelite christology, as well as maximian's anthropology and soteriology. Reexamining the meaning and place of the gnome in the theological thought of this saint can help in better understanding the importance of the reality of the will in the framework of christological discussions of the seventh century. The focus of the research is reflected in the consideration of the ontological status of the gnome in the Disputation with Pyrrhus, where saint Maximus provides an authentic interpretation of the will, placing it in a direct relationship with christology, soteriology, and, finally, eschatology. On those grounds, the direction of the research is directed towards the reception of the term gnome to saint Maximus, in order to point out the new meanings he provides. Such a perspective brings the gnome into connection with the concept of proeresis, which is directed to the same reality, the reality of the will. Observing the similarities and differences between these two concepts leads to the central moment of maximian's diotelism, to the relationship between the natural will and the gnome, whereby the research is directed towards the eschatological perspective of the gnome, where the final answer to the ontological status of the gnome in the theological opus of Saint Maximus will be given.